Development of a Python-Based MasterCurveCreator Tool for Viscoelastic Materials - Sharma, Harshita; Albrecht, Jan; Horn, Tobias Daniel; Pantou, Remi; Rzepka, Sven (2025 Smart Systems Integration Conference and Exhibition (SSI), 2025)
The behavior of viscoelastic materials across wide range of temperatures and frequencies is essential for engineering applications, significantly impacting the performance, durability and safety of products in industries like automotive and aerospace. To understand this behavior, master curves are very helpful, as they consolidate the viscoelastic behavior into single curve and predicts the material properties under varying conditions. Traditionally, to create master curves has required considerable manual effort and is prone to human error, which leads to inaccurate results. To streamline this process, MasterCurveCreator, a python-based tool with an intuitive GUI, is developed to generate master curves. This tool shifts raw measurement data using temperature-dependent shift factors derived from a Power Law model, adjusts to a reference temperature and generates a master curve. In addition, it supports the deduction of the Prony series coefficients for effective modeling of viscoelastic behavior.